PENGARUH TINGKAT PENDIDIKAN, PERTUMBUHAN EKONOMI DAN INVESTASI TERHADAP TINGKAT PENGANGGURAN DI KABUPATEN MIMIKA - Klanisa J. N. Korisano; Benedikta Chesy Aristya Mego Dona; Fani Kristin Ohee (ADMIN: Jurnal Administrasi Negara, 2025)
This study aims to determine the effect of education level, economic growth, and investment on the unemployment in Mimika Regency, both partially and simulaneously. The method used is this study is associative. The data collection technique employed by the researchers is the documentary technique that has been collected and published by the Central Statistics Agency. The analysis tool used in this research is multipe linear regression. The results of the study indicate that partially, education level, economic growth and investment do not have a significant effect on the unemployment rate in Mimika Regency. Simultaneously, education level, economic growth, and investment also do not have a significant effect on the unemployment rate in Mimika Regency.